A method for preparing a boron nitride setter plate
By maleic anhydride and aminoation of hexagonal boron nitride powder and boron nitride fibers, and aluminum sol is introduced in the secondary composite step to form a crosslinked mesh structure, the problems of low thermal conductivity and insufficient bending strength of the boron nitride sintered plate are solved, and efficient heat transfer and long-life use are achieved.
Patent Information
- Application Number
- CN202510097512.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-22
AI Technical Summary
The existing boron nitride sintering plates have low thermal conductivity and insufficient bending strength during high-temperature sintering. The bending strength significantly decreases after repeated hot and cold cycles, resulting in a shortened service life.
Hexagonal boron nitride powder is used as the matrix and boron nitride fibers are used as the reinforced phase. The bonding force between the powder and the fiber is improved by maleic anhydration and aminoation treatment, a cross-linked network structure is formed, thermal conductivity and bending strength are improved, and aluminum sol is introduced in the secondary composite step for epoxy modification to enhance the binding force.
The thermal conductivity and bending strength of the boron nitride burned plate are significantly improved, so that it can maintain a high bending strength after repeated hot and cold cycles, and extend its service life.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of boron nitride setter plates, and particularly relates to a preparation method of a boron nitride setter plate. Background Art
[0002] With the widespread development of microelectronic devices, high thermal conductivity aluminum nitride ceramics and silicon nitride ceramics as matrix materials or packaging materials have received widespread attention and application; in the production process of aluminum nitride ceramics and silicon nitride ceramic products, sintering is one of the key production processes, which is used to sinter aluminum nitride ceramics and silicon nitride ceramic green sheets at high temperatures to transform them into corresponding ceramic products.
[0003] During the sintering process of aluminum nitride ceramics and silicon nitride ceramics, there are many factors that affect the product quality, among which the quality of the support plate used for sintering is a very critical factor; the support plate is a carrier for sintering aluminum nitride ceramics and silicon nitride ceramics, and its quality and performance have a direct impact on the quality, output, energy consumption and cost of fired aluminum nitride ceramics and silicon nitride ceramic products; during use, the support plate must not only withstand the high temperature sintering temperature and the pressure brought by the fired ceramic products, but also withstand repeated hot and cold cycles, so it is required to have the characteristics of high temperature resistance, high mechanical strength, stable chemical properties, good thermal shock stability and long service life.
[0004] Boron nitride materials have the advantages of low thermal expansion coefficient, high thermal conductivity, good thermal shock resistance, good high-temperature chemical stability, good peeling properties of solidified materials, and non-wetting with molten metal. They are now widely used in the fields of crucibles for smelting metals, pipes for conveying liquid metals, and casting molds, and can meet the demand for the use of high-performance refractory materials in special smelting processes.
[0005] However, the toughness of boron nitride materials is poor. They are prone to bending deformation and fracture when subjected to bending force, and have low bending strength, which affects the reusability of the boron nitride support plate and shortens its service life. The existing technology usually improves the toughness of boron nitride materials by adding reinforcing phases, such as nanofibers such as boron nitride fibers, which can prevent further crack expansion through a bridging effect and better resist external damage. They can also increase the crack expansion distance and slow down the crack expansion rate through reinforcement mechanisms such as crack deflection, thereby improving the bending strength of the boron nitride material. However, the interface bonding strength between the nanofibers and the boron nitride powder is weak, which causes the nanofibers to be easily pulled out of the boron nitride matrix or broken when subjected to force, thereby failing to effectively prevent crack expansion. In addition, since the nanofibers have a high specific surface area, they are prone to agglomeration, making it difficult to evenly distribute them in the boron nitride matrix, which reduces the reinforcement effect and reduces the overall stability.
[0006] The boron nitride support plate prepared by the existing technology has a low thermal conductivity. During the sintering process, it cannot effectively disperse and transfer heat, resulting in local overheating and thermal stress concentration, which is not conducive to achieving uniform temperature distribution and increases the difficulty of sintering. Moreover, when nanofibers are used as the toughening phase, the bending strength decreases significantly after repeated hot and cold cycles, greatly shortening the service life of the boron nitride support plate. Summary of the invention
[0007] In order to solve the technical problems existing in the prior art, the present invention provides a method for preparing a boron nitride support plate, which improves thermal conductivity and bending strength, and can still maintain a high bending strength after repeated hot and cold cycles.
[0008] In view of the above technical problems, the present invention adopts the following technical solutions:
[0009] A method for preparing a boron nitride setter plate includes the steps of mixing, cold isostatic pressing and vacuum sintering. The specific operations are as follows:
[0010] 1. Mixing
[0011] Put hexagonal boron nitride powder with a particle size of 100-200nm, hexagonal boron nitride powder with a particle size of 1.0-3.0μm, hexagonal boron nitride powder with a particle size of 4.0-10.0μm, ammonium bicarbonate, phenolic resin, and sodium tripolyphosphate in a ball mill, add anhydrous ethanol for ball milling, the ball milling time is 0.8-1.2h, the ball milling speed is 88-92rpm, then add the secondary compound and continue ball milling for 23-28min, and after the ball milling is completed, dry at 87-92°C to obtain a dry powder;
[0012] The mass ratio of the hexagonal boron nitride powder with a particle size of 100-200 nm, the hexagonal boron nitride powder with a particle size of 1.0-3.0 μm, the hexagonal boron nitride powder with a particle size of 4.0-10.0 μm, ammonium bicarbonate, phenolic resin, sodium tripolyphosphate, anhydrous ethanol and the secondary composite is 8.0-12.0:25.0-30.0:58.0-67.0:2.8-3.2:2.6-3.0:1.1-1.5:226-235:12.2-12.6;
[0013] The method for preparing the secondary composite comprises the steps of preparing amino-treated boron nitride fiber, preparing maleic anhydride-treated boron nitride powder, primary composite and secondary composite, and the specific operations are as follows:
[0014] (1) Preparation of amino-modified boron nitride fibers
[0015] The preparation method of the aminated boron nitride fiber comprises the following steps: placing the boron nitride fiber in a nitric acid solution, raising the temperature to 117-122° C. for hydrothermal reaction, the reaction time being 4.8-5.2 hours, filtering, washing, and drying after the reaction is completed to obtain the pretreated boron nitride fiber; placing the pretreated boron nitride fiber in acetone, adding polyethylene glycol monolaurate and stirring evenly, adding N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, raising the temperature to 68-72° C., keeping the temperature for reaction for 5.8-6.2 hours, filtering, washing, and drying after the reaction is completed to obtain the aminated boron nitride fiber;
[0016] The boron nitride fiber has a diameter of 58-62 nm and a length of 0.4-0.6 μm;
[0017] The mass ratio of the boron nitride fiber to the nitric acid solution is 14.7-15.2:495-504;
[0018] The mass concentration of the nitric acid solution is 63-67%;
[0019] The mass ratio of the pretreated boron nitride fiber, acetone, polyethylene glycol monolaurate and N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane is 12.2-12.7:146-155:1.8-2.2:1.2-1.6;
[0020] (2) Preparation of maleic anhydride boron nitride powder
[0021] The hexagonal boron nitride powder is subjected to radio frequency discharge modification treatment by air plasma, the air flow rate is controlled to be 336-343 mL / min, the treatment power is 216-224 W, and the treatment time is 5.8-6.2 min. After the treatment, the surface hydroxylated hexagonal boron nitride powder is obtained; the surface hydroxylated hexagonal boron nitride powder is placed in a reaction container, ethyl acetate is introduced and stirred evenly, maleic anhydride and perchloric acid are added, and the mixture is stirred at 312-327 rpm for 1.8-2.2 h. After the stirring is completed, the temperature is increased to 60-64° C., and the reaction is stirred at a speed of 4.3-4.6 h. After the reaction is completed, the mixture is filtered, washed, and dried to obtain maleic anhydride boron nitride powder;
[0022] The particle size of the hexagonal boron nitride powder is 90-110 nm;
[0023] The mass volume ratio of the surface hydroxylated hexagonal boron nitride powder, ethyl acetate, maleic anhydride, and perchloric acid is 4.7-5.2 g: 790-810 mL: 14.1-14.5 g: 117-123 mL;
[0024] (3) One-time compound
[0025] The amino-treated boron nitride fiber is placed in dimethyl sulfoxide, stirred evenly, and then maleic anhydride-treated boron nitride powder is added, and ultrasonic oscillation is performed. The ultrasonic time is 1.8-2.2 hours, the ultrasonic frequency is 35-40kHz, the ultrasonic power is 146-155W, and the ultrasonic temperature is 80-84°C. After the ultrasonic treatment is completed, the stirring reaction is continued for 5.8-6.2 hours. After the reaction is completed, the reaction is centrifuged, washed, and dried to obtain a primary composite;
[0026] The mass volume ratio of the amino boron nitride fiber, dimethyl sulfoxide, and maleic anhydride boron nitride powder is 9.7-10.2 g: 246-255 mL: 4.6-5.0 g;
[0027] (4) Secondary compound
[0028] Add deionized water and the primary complex to the reaction container, stir evenly, add an aqueous solution of aluminum nitrate, stir evenly, add a tartaric acid solution and hexadecyltrimethylammonium bromide, then add an aqueous ammonia solution to adjust the pH to 8.2-8.8, perform ultrasonic treatment, the ultrasonic time is 35-40 minutes, the ultrasonic power is 104-115W, and the ultrasonic frequency is 22-27kHz. After the ultrasonic treatment, stir for 3.8-4.2 hours, and then stand for aging for 9.7-10.2 hours, add γ-glycidyloxypropylmethyldiethoxysilane, increase the temperature to 60-64°C, stir and react for 3.8-4.2 hours, after the reaction, wash, dry at 78-82°C for 9.8-10.3 hours, wait for it to naturally return to room temperature, and heat to 225-233°C at 1.8-2.2°C / min in a nitrogen atmosphere, and keep warm for 3.8-4.2 hours to obtain a secondary complex;
[0029] The mass ratio of the deionized water, the primary complex, the aluminum nitrate aqueous solution, the tartaric acid solution, the hexadecyltrimethylammonium bromide, and the γ-glycidyloxypropylmethyldiethoxysilane is 49.2-50.6:9.8-10.2:66.4-67.0:9.0-9.5:1.0-1.3:0.72-0.77;
[0030] The mass concentration of the aluminum nitrate aqueous solution is 2.8-3.3%;
[0031] The mass concentration of the tartaric acid solution is 1.8-2.2%;
[0032] The mass concentration of the ammonia solution is 20-24%.
[0033] 2. Cold isostatic pressing
[0034] The dry powder is added into a cold pressing mold, and after compaction, it is put into a cold isostatic press for cold isostatic pressing. The pressure of the cold isostatic pressing is controlled to be 70-100 MPa, and the holding time is 10-20 min to obtain a blank.
[0035] 3. Vacuum sintering
[0036] The blank is placed in a vacuum high-temperature furnace and sintered in a nitrogen atmosphere. The vacuum degree is controlled to be 8-12Pa, the sintering temperature is 1850-2000°C, the insulation time is 4.0-8.0h, and the blank is cooled to room temperature with the furnace to obtain a boron nitride support plate.
[0037] Compared with the prior art, the present invention has achieved the following beneficial effects:
[0038] 1. In the preparation of the boron nitride setter plate, the present invention uses hexagonal boron nitride powder as a matrix and boron nitride fiber as a reinforcing phase. The hexagonal boron nitride powder is firstly subjected to maleic anhydride treatment so that the hexagonal boron nitride powder contains anhydride groups. Specifically, the hexagonal boron nitride powder is firstly subjected to plasma treatment so that the surface thereof contains more hydroxyl groups. Maleic anhydride is then added for anhydride treatment. Then, the boron nitride fiber is amino treated. Specifically, a surface dispersant and an aminosilane coupling agent are used for treatment so that the surface of the boron nitride fiber has more amino groups. In the first composite step, the amino groups of the boron nitride fiber react with the anhydride groups of the hexagonal boron nitride powder. The two are firmly combined, thereby improving the bending strength of the setter plate. Then, in the second composite step, the hexagonal boron nitride powder is subjected to a maleic anhydride treatment so that the hexagonal boron nitride powder contains more hydroxyl groups. Aluminum sol is added and modified with epoxy groups, so that the surface of the aluminum sol contains more epoxy groups. The epoxy groups can react with the amino groups of the primary composite, thereby enhancing the bonding force between aluminum oxide and the primary composite, making the bonding between hexagonal boron nitride powder, boron nitride fiber and aluminum oxide stable, forming a cross-linked network structure, and both boron nitride fiber and aluminum oxide have high thermal conductivity, thereby improving the thermal conductivity of the product, and the secondary composite has good dispersibility and compatibility with other components, thereby ensuring the homogeneity and stability of the dry powder, and finally making the prepared product have uniform porosity, high bending strength and good stability, and still maintain excellent bending strength after repeated hot and cold cycles, thereby extending the service life of the boron nitride setter;
[0039] 2. The boron nitride setter plate prepared by the method of the present invention has a density of 1.52-1.60 g / cm 3 , porosity is 27-30%, flexural strength is 37.2-39.8MPa, thermal conductivity is 46.2-48.1 W / (m·k);
[0040] 3. The boron nitride support plate prepared by the method of the present invention was heated to 1900°C at a rate of 50°C / min in an air atmosphere, kept warm for 12.0 hours, and then cooled to 20°C at a rate of 30°C / min. This was regarded as one cycle. 20 cycles were performed continuously, and the bending strength of the boron nitride support plate was measured again to be 36.4-39.3MPa. DETAILED DESCRIPTION
[0041] In order to more clearly understand the technical features, purposes and effects of the present invention, specific embodiments of the present invention are now described.
[0042] Example 1
[0043] 1. Mixing
[0044] 10.0 g of hexagonal boron nitride powder with a particle size of 150 nm, 28.0 g of hexagonal boron nitride powder with a particle size of 2.0 μm, 62.0 g of hexagonal boron nitride powder with a particle size of 7.0 μm, 3.0 g of ammonium bicarbonate, 2.8 g of phenolic resin, and 1.3 g of sodium tripolyphosphate were placed in a ball mill, and 230 g of anhydrous ethanol was added for ball milling. The ball milling time was 1.0 h, and the ball milling speed was 90 rpm. Then, 12.4 g of the secondary compound was added and the ball milling was continued for 25 min. After the ball milling was completed, it was dried at 90° C. to obtain a dry powder;
[0045] The method for preparing the secondary composite comprises the steps of preparing amino-treated boron nitride fiber, preparing maleic anhydride-treated boron nitride powder, primary composite and secondary composite, and the specific operations are as follows:
[0046] (1) Preparation of amino-modified boron nitride fibers
[0047] The preparation method of the aminated boron nitride fiber is as follows: 15.0g of the boron nitride fiber is placed in 500g of a 65wt% nitric acid solution, the temperature is increased to 120°C for hydrothermal reaction, the reaction time is 5.0h, after the reaction is completed, filtering, washing, and drying to obtain the pretreated boron nitride fiber; 12.5g of the pretreated boron nitride fiber is placed in 150g of acetone, 2.0g of polyethylene glycol monolaurate is added, stirred evenly, 1.4g of N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane is added, the temperature is increased to 70°C, the temperature is kept for reaction for 6.0h, after the reaction is completed, filtering, washing, and drying to obtain the aminated boron nitride fiber;
[0048] The boron nitride fiber has a diameter of 60 nm and a length of 0.5 μm;
[0049] (2) Preparation of maleic anhydride boron nitride powder
[0050] The hexagonal boron nitride powder was subjected to radio frequency discharge modification treatment by air plasma, and the air flow rate was controlled to be 340 mL / min, the treatment power was 220 W, and the treatment time was 6.0 min. After the treatment, the surface hydroxylated hexagonal boron nitride powder was obtained; 5.0 g of the surface hydroxylated hexagonal boron nitride powder was placed in a reaction container, 800 mL of ethyl acetate was introduced and stirred evenly, and then 14.3 g of maleic anhydride and 120 mL of perchloric acid were added, and stirred at 320 rpm for 2.0 h. After the stirring was completed, the temperature was increased to 62° C., and the stirring speed was maintained for 4.5 h. After the reaction was completed, the maleic anhydride boron nitride powder was obtained by filtration, washing and drying;
[0051] The particle size of the hexagonal boron nitride powder is 100 nm;
[0052] (3) One-time compound
[0053] 10.0 g of amino-treated boron nitride fiber was placed in 250 mL of dimethyl sulfoxide, and after being stirred evenly, 4.8 g of maleic anhydride-treated boron nitride powder was added, and ultrasonic oscillation was performed. The ultrasonic time was 2.0 h, the ultrasonic frequency was 37 kHz, the ultrasonic power was 150 W, and the ultrasonic temperature was 82 ° C. After the ultrasonic treatment, the reaction was continued to stir for 6.0 h. After the reaction was completed, the reaction was centrifuged, washed, and dried to obtain a primary composite;
[0054] (4) Secondary compound
[0055] 50.0g of deionized water and 10.0g of the primary composite were added to the reaction container, and after stirring, 66.7g of 3.0wt% aluminum nitrate aqueous solution was added, and after stirring, 9.2g of 2.0wt% tartaric acid solution and 1.1g of hexadecyltrimethylammonium bromide were added, and then 22wt% ammonia aqueous solution was added to adjust the pH to 8.5, and ultrasonic treatment was performed. The ultrasonic time was 37min, the ultrasonic power was 110W, and the ultrasonic frequency was 25kHz. After the ultrasonic treatment, it was stirred for 4.0h, and then allowed to stand for aging for 10.0h, 0.75g of γ-glycidyl ether oxypropyl methyl diethoxy silane was added, the temperature was raised to 62°C, and the reaction was stirred for 4.0h. After the reaction was completed, it was washed and dried at 80°C for 10.0h, and then naturally recovered to room temperature. In a nitrogen atmosphere, the temperature was raised to 230°C at 2.0°C / min and kept warm for 4.0h to obtain a secondary composite.
[0056] 2. Cold isostatic pressing
[0057] The dry powder is added into the cold pressing mold, and after compaction, it is put into the cold isostatic press for cold isostatic pressing. The pressure of the cold isostatic pressing is controlled to be 85 MPa, and the holding time is 15 min to obtain a blank.
[0058] 3. Vacuum sintering
[0059] The blank was placed in a vacuum high-temperature furnace and sintered in a nitrogen atmosphere. The vacuum degree was controlled to be 10 Pa, the sintering temperature was 1900° C., the insulation time was 5.0 h, and the blank was cooled to room temperature with the furnace to obtain a boron nitride support plate.
[0060] Example 2
[0061] 1. Mixing
[0062] 8.0 g of hexagonal boron nitride powder with a particle size of 100 nm, 25.0 g of hexagonal boron nitride powder with a particle size of 3.0 μm, 67.0 g of hexagonal boron nitride powder with a particle size of 4.0 μm, 2.8 g of ammonium bicarbonate, 2.6 g of phenolic resin, and 1.1 g of sodium tripolyphosphate were placed in a ball mill, and 226 g of anhydrous ethanol was added for ball milling. The ball milling time was 0.8 h, and the ball milling speed was 88 rpm. Then, 12.2 g of the secondary composite was added and the ball milling was continued for 23 min. After the ball milling was completed, it was dried at 87° C. to obtain a dry powder;
[0063] The method for preparing the secondary composite comprises the steps of preparing amino-treated boron nitride fiber, preparing maleic anhydride-treated boron nitride powder, primary composite and secondary composite, and the specific operations are as follows:
[0064] (1) Preparation of amino-modified boron nitride fibers
[0065] The preparation method of the aminated boron nitride fiber is as follows: 14.7g of the boron nitride fiber is placed in 495g of a 63wt% nitric acid solution, the temperature is increased to 117°C for hydrothermal reaction, the reaction time is 4.8h, after the reaction is completed, filtering, washing, and drying to obtain the pretreated boron nitride fiber; 12.2g of the pretreated boron nitride fiber is placed in 146g of acetone, 1.8g of polyethylene glycol monolaurate is added, stirred evenly, 1.2g of N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane is added, the temperature is increased to 68°C, the reaction is kept warm for 5.8h, after the reaction is completed, filtering, washing, and drying to obtain the aminated boron nitride fiber;
[0066] The boron nitride fiber has a diameter of 58 nm and a length of 0.4 μm;
[0067] (2) Preparation of maleic anhydride boron nitride powder
[0068] The hexagonal boron nitride powder was subjected to radio frequency discharge modification treatment by air plasma, and the air flow rate was controlled to be 336 mL / min, the treatment power was 216 W, and the treatment time was 5.8 min. After the treatment, the surface hydroxylated hexagonal boron nitride powder was obtained; 4.7 g of the surface hydroxylated hexagonal boron nitride powder was placed in a reaction container, 790 mL of ethyl acetate was introduced and stirred evenly, and then 14.1 g of maleic anhydride and 117 mL of perchloric acid were added, and stirred at 312 rpm for 1.8 h. After the stirring was completed, the temperature was increased to 60°C, and the speed was maintained to stir the reaction for 4.3 h. After the reaction was completed, the maleic anhydride boron nitride powder was obtained by filtration, washing and drying;
[0069] The particle size of the hexagonal boron nitride powder is 90 nm;
[0070] (3) One-time compound
[0071] 9.7 g of amino-treated boron nitride fiber was placed in 246 mL of dimethyl sulfoxide, and after being stirred evenly, 4.6 g of maleic anhydride-treated boron nitride powder was added, and ultrasonic oscillation was performed. The ultrasonic time was 1.8 h, the ultrasonic frequency was 35 kHz, the ultrasonic power was 146 W, and the ultrasonic temperature was 80 ° C. After the ultrasonic treatment, the reaction was continued to stir for 5.8 h. After the reaction was completed, the reaction was centrifuged, washed, and dried to obtain a primary composite;
[0072] (4) Secondary compound
[0073] 49.2 g of deionized water and 9.8 g of the primary composite were added to the reaction container, and after stirring, 66.4 g of 2.8 wt% aluminum nitrate aqueous solution was added, and after stirring, 9.0 g of 1.8 wt% tartaric acid solution and 1.0 g of hexadecyltrimethylammonium bromide were added, and then 20 wt% ammonia aqueous solution was added to adjust the pH to 8.2, and ultrasonic treatment was performed. The ultrasonic time was 35 min, the ultrasonic power was 104 W, and the ultrasonic frequency was 22 kHz. After the ultrasonic treatment, it was stirred for 3.8 h, and then allowed to stand for aging for 9.7 h, 0.72 g of γ-glycidyl ether oxypropyl methyl diethoxy silane was added, the temperature was raised to 60 ° C, and the reaction was stirred for 3.8 h. After the reaction was completed, it was washed and dried at 78 ° C for 9.8 h, and then naturally recovered to room temperature. In a nitrogen atmosphere, the temperature was raised to 225 ° C at 1.8 ° C / min, and kept warm for 3.8 h to obtain a secondary composite.
[0074] 2. Cold isostatic pressing
[0075] The dry powder is added into a cold pressing mold, and after compaction, it is put into a cold isostatic press for cold isostatic pressing. The pressure of the cold isostatic pressing is controlled to be 70 MPa, and the holding time is 20 min to obtain a blank.
[0076] 3. Vacuum sintering
[0077] The blank was placed in a vacuum high-temperature furnace and sintered in a nitrogen atmosphere. The vacuum degree was controlled to be 8 Pa, the sintering temperature was 1850°C, the insulation time was 8.0 h, and the blank was cooled to room temperature with the furnace to obtain a boron nitride support plate.
[0078] Example 3
[0079] 1. Mixing
[0080] 12.0 g of hexagonal boron nitride powder with a particle size of 200 nm, 30.0 g of hexagonal boron nitride powder with a particle size of 1.0 μm, 58.0 g of hexagonal boron nitride powder with a particle size of 10.0 μm, 3.2 g of ammonium bicarbonate, 3.0 g of phenolic resin, and 1.5 g of sodium tripolyphosphate were placed in a ball mill, and 235 g of anhydrous ethanol was added for ball milling. The ball milling time was 1.2 h, and the ball milling speed was 92 rpm. Then, 12.6 g of the secondary composite was added and the ball milling was continued for 28 min. After the ball milling was completed, it was dried at 92° C. to obtain a dry powder;
[0081] The method for preparing the secondary composite comprises the steps of preparing amino-treated boron nitride fiber, preparing maleic anhydride-treated boron nitride powder, primary composite and secondary composite, and the specific operations are as follows:
[0082] (1) Preparation of amino-modified boron nitride fibers
[0083] The preparation method of the aminated boron nitride fiber is as follows: 15.2g of the boron nitride fiber is placed in 504g of a 67wt% nitric acid solution, the temperature is increased to 122°C for hydrothermal reaction, the reaction time is 5.2h, after the reaction is completed, filtering, washing, and drying to obtain the pretreated boron nitride fiber; 12.7g of the pretreated boron nitride fiber is placed in 155g of acetone, 2.2g of polyethylene glycol monolaurate is added, stirred evenly, 1.6g of N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane is added, the temperature is increased to 72°C, and the reaction is kept warm for 6.2h, after the reaction is completed, filtering, washing, and drying to obtain the aminated boron nitride fiber;
[0084] The boron nitride fiber has a diameter of 62 nm and a length of 0.6 μm;
[0085] (2) Preparation of maleic anhydride boron nitride powder
[0086] The hexagonal boron nitride powder was modified by radio frequency discharge using air plasma, and the air flow rate was controlled to be 343 mL / min, the processing power was 224 W, and the processing time was 6.2 min. After the treatment, the surface hydroxylated hexagonal boron nitride powder was obtained; 5.2 g of the surface hydroxylated hexagonal boron nitride powder was placed in a reaction container, 810 mL of ethyl acetate was introduced and stirred evenly, and then 14.5 g of maleic anhydride and 123 mL of perchloric acid were added, and stirred at 327 rpm for 2.2 h. After the stirring was completed, the temperature was increased to 64 ° C, and the speed was maintained to stir the reaction for 4.6 h. After the reaction was completed, it was filtered, washed, and dried to obtain maleic anhydride boron nitride powder;
[0087] The particle size of the hexagonal boron nitride powder is 110 nm;
[0088] (3) One-time compound
[0089] 10.2 g of amino-treated boron nitride fiber was placed in 255 mL of dimethyl sulfoxide, and after being stirred evenly, 5.0 g of maleic anhydride-treated boron nitride powder was added, and ultrasonic oscillation was performed. The ultrasonic time was 2.2 h, the ultrasonic frequency was 40 kHz, the ultrasonic power was 155 W, and the ultrasonic temperature was 84 ° C. After the ultrasonic treatment, the reaction was continued to stir for 6.2 h. After the reaction was completed, the reaction was centrifuged, washed, and dried to obtain a primary composite;
[0090] (4) Secondary compound
[0091] 50.6 g of deionized water and 10.2 g of the primary composite were added to the reaction container, and after stirring, 67.0 g of 3.3 wt % aluminum nitrate aqueous solution was added, and after stirring, 9.5 g of 2.2 wt % tartaric acid solution and 1.3 g of hexadecyltrimethylammonium bromide were added, and then 24 wt % ammonia aqueous solution was added to adjust the pH to 8.8, and ultrasonic treatment was performed. The ultrasonic time was 405 min, the ultrasonic power was 115 W, and the ultrasonic frequency was 27 kHz. After the ultrasonic treatment, it was stirred for 4.2 h, and then allowed to stand for aging for 10.2 h, 0.77 g of γ-glycidyl ether oxypropyl methyl diethoxy silane was added, the temperature was raised to 64 ° C, and the reaction was stirred for 4.2 h. After the reaction was completed, it was washed and dried at 82 ° C for 10.3 h, and then naturally recovered to room temperature. In a nitrogen atmosphere, the temperature was raised to 233 ° C at 2.2 ° C / min, and kept warm for 4.2 h to obtain a secondary composite.
[0092] 2. Cold isostatic pressing
[0093] The dry powder is added into a cold pressing mold, and after compaction, it is put into a cold isostatic press for cold isostatic pressing. The pressure of the cold isostatic pressing is controlled to be 100 MPa, and the holding time is 10 min to obtain a blank.
[0094] 3. Vacuum sintering
[0095] The blank was placed in a vacuum high-temperature furnace and sintered in a nitrogen atmosphere. The vacuum degree was controlled to be 12 Pa, the sintering temperature was 2000°C, the insulation time was 4.0 h, and the blank was cooled to room temperature with the furnace to obtain a boron nitride support plate.
[0096] Comparative Example 1
[0097] Based on Example 1, the changes are that in the mixing step,
[0098] In the method for preparing the secondary composite, the steps of preparing amino-treated boron nitride fiber and maleic anhydride-treated boron nitride powder are omitted;
[0099] In a composite step, an equal amount of amino-treated boron nitride fibers are replaced with untreated boron nitride fibers, wherein the diameter of the boron nitride fibers is 20 nm and the length is 0.5 μm; an equal amount of maleic anhydride-treated boron nitride powder is replaced with untreated hexagonal boron nitride powder, wherein the particle size of the hexagonal boron nitride powder is 100 nm;
[0100] The rest of the operations are the same.
[0101] Comparative Example 2
[0102] Based on Example 1, the changes are that in the mixing step,
[0103] In the preparation method of the secondary composite, the secondary composite step is to add 50.0g of deionized water and 10.0g of the primary composite into a reaction container, stir evenly, add 2.0g of aluminum oxide, stir evenly, filter, wash and dry to obtain the secondary composite;
[0104] The rest of the operations are the same.
[0105] Performance Testing
[0106] The boron nitride setter plates prepared in Examples 1-3 and Comparative Examples 1-2 were subjected to performance tests, as follows:
[0107]
[0108] The bending strength after the hot and cold cycle is specifically determined by heating the boron nitride setter plates prepared in Examples 1-3 and Comparative Examples 1-2 to 1900°C at a rate of 50°C / min in an air atmosphere, keeping the temperature for 12.0 hours, and then cooling the temperature to 20°C at a rate of 30°C / min. This is regarded as one cycle, and 20 cycles are performed continuously to test the bending strength of the boron nitride setter plates again.
[0109] In the preparation of the boron nitride setter plate, the present invention uses hexagonal boron nitride powder as a matrix and boron nitride fiber as a reinforcing phase. The hexagonal boron nitride powder is firstly subjected to maleic anhydride treatment so that the hexagonal boron nitride powder contains anhydride groups. Specifically, the hexagonal boron nitride powder is firstly subjected to plasma treatment so that the surface thereof contains more hydroxyl groups. Maleic anhydride is then added for anhydride treatment. Then, the boron nitride fiber is amino treated. Specifically, a surface dispersant and an aminosilane coupling agent are used for treatment so that the surface of the boron nitride fiber has more amino groups. In a first composite step, the amino groups of the boron nitride fiber react with the anhydride groups of the hexagonal boron nitride powder. The two are firmly combined, thereby improving the bending strength of the setter plate. Then, in a second composite step, the boron nitride fiber is introduced. Alumina sol is prepared and modified with epoxy groups so that the surface of the aluminum sol contains more epoxy groups. The epoxy groups can react with the amino groups of the primary composite, thereby enhancing the bonding force between alumina and the primary composite, and making the bonding between hexagonal boron nitride powder, boron nitride fiber and alumina stable, forming a cross-linked network structure, and both boron nitride fiber and alumina have high thermal conductivity, thereby improving the thermal conductivity of the product, and the secondary composite has good dispersibility and compatibility with other components, thereby ensuring the homogeneity and stability of the dry powder, and ultimately making the product have uniform porosity, high bending strength and good stability, and after repeated hot and cold cycles, it still maintains excellent bending strength, thereby extending the service life of the boron nitride support plate.
[0110] Comparative Example 1 omits the preparation of maleic anhydride-treated boron nitride powder and amino-treated boron nitride fiber. In the compounding step, the hexagonal boron nitride powder and the boron nitride fiber have poor dispersion and strong agglomeration, and the homogeneity of the primary composite is poor, which affects the uniformity of the secondary composite, and ultimately makes the strength of the boron nitride support plate uneven. In addition, the reinforcing properties and thermal conductivity of the boron nitride fiber cannot be fully utilized, and the product has poor bending strength and stability. In Comparative Example 2, in the secondary compounding step, the primary composite is mixed with alumina, and the bonding force between the two is poor, and the stability is poor, which also affects the strength and thermal conductivity of the boron nitride support plate and weakens the stability.
[0111] Unless otherwise specified, all percentages used in the present invention are by mass.
[0112] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a boron nitride setter plate, characterized in that: It includes the steps of mixing, cold isostatic pressing and vacuum sintering; The mixing step comprises placing hexagonal boron nitride powder with a particle size of 100-200 nm, hexagonal boron nitride powder with a particle size of 1.0-3.0 μm, hexagonal boron nitride powder with a particle size of 4.0-10.0 μm, ammonium bicarbonate, phenolic resin, and sodium tripolyphosphate in a ball milling device, adding anhydrous ethanol for ball milling, then adding the secondary composite and continuing ball milling for 23-28 minutes, and drying at 87-92° C. after the ball milling to obtain a dry powder; The method for preparing the secondary composite comprises the steps of preparing amino-treated boron nitride fiber, preparing maleic anhydride-treated boron nitride powder, primary composite and secondary composite. The step of preparing the aminated boron nitride fiber is as follows: placing the pretreated boron nitride fiber in acetone, adding polyethylene glycol monolaurate and stirring evenly, adding N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, raising the temperature to 68-72° C., keeping the temperature for reaction for 5.8-6.2 hours, filtering, washing and drying after the reaction is completed, to obtain the aminated boron nitride fiber; The steps of preparing maleic anhydride boron nitride powder are as follows: performing radio frequency discharge modification treatment on hexagonal boron nitride powder by air plasma to obtain surface hydroxylated hexagonal boron nitride powder; placing the surface hydroxylated hexagonal boron nitride powder in a reaction container, introducing ethyl acetate and stirring evenly, adding maleic anhydride and perchloric acid, stirring for 1.8-2.2 hours, and after the stirring is completed, raising the temperature to 60-64° C., maintaining the speed and stirring for 4.3-4.6 hours, and after the reaction is completed, filtering, washing, and drying to obtain maleic anhydride boron nitride powder; The first composite step is to place the amino boron nitride fiber in dimethyl sulfoxide, stir evenly, add maleic anhydride boron nitride powder, and perform ultrasonic oscillation at a temperature of 80-84° C. After the ultrasonic treatment, continue stirring and reacting for 5.8-6.2 hours. After the reaction, centrifuge, wash and dry to obtain a first composite; The secondary compounding step comprises: adding deionized water and the primary compound into a reaction container, stirring evenly, adding an aqueous solution of aluminum nitrate, stirring evenly, adding a tartaric acid solution and hexadecyltrimethylammonium bromide, and then adding an aqueous solution of ammonia to adjust the pH to 8.2-8.8, performing ultrasonic treatment, stirring for 3.8-4.2 hours after the ultrasonic treatment, and then standing and aging for 9.7-10.2 hours, adding γ-glycidyloxypropylmethyldiethoxysilane, raising the temperature to 60-64° C., stirring and reacting for 3.8-4.2 hours, and after the reaction, washing and drying, and then naturally recovering to room temperature, heating to 225-233° C. at 1.8-2.2° C. / min in a nitrogen atmosphere, and keeping the temperature for 3.8-4.2 hours to obtain a secondary compound.
2. The method for preparing a boron nitride setter according to claim 1, characterized in that: In the mixing step, the ball milling treatment has a ball milling time of 0.8-1.2h and a ball milling speed of 88-92rpm; The mass ratio of the hexagonal boron nitride powder with a particle size of 100-200 nm, the hexagonal boron nitride powder with a particle size of 1.0-3.0 μm, the hexagonal boron nitride powder with a particle size of 4.0-10.0 μm, ammonium bicarbonate, phenolic resin, sodium tripolyphosphate, anhydrous ethanol and the secondary composite is 8.0-12.0:25.0-30.0:58.0-67.0:2.8-3.2:2.6-3.0:1.1-1.5:226-235:12.2-12.
6.
3. The method for preparing a boron nitride setter according to claim 1, characterized in that: In the step of preparing the amino-treated boron nitride fiber, the mass ratio of the pretreated boron nitride fiber, acetone, polyethylene glycol monolaurate and N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane is 12.2-12.7:146-155:1.8-2.2:1.2-1.
6.
4. The method for preparing a boron nitride setter according to claim 1, characterized in that: The preparation method of the pretreated boron nitride fiber is as follows: placing the boron nitride fiber in a nitric acid solution, raising the temperature to 117-122° C. for hydrothermal reaction, the reaction time being 4.8-5.2 hours, and after the reaction is completed, filtering, washing, and drying to obtain the pretreated boron nitride fiber; The boron nitride fiber has a diameter of 58-62 nm and a length of 0.4-0.6 μm; The mass ratio of the boron nitride fiber to the nitric acid solution is 14.7-15.2:495-504; The mass concentration of the nitric acid solution is 63-67%.
5. The method for preparing a boron nitride setter according to claim 1, characterized in that: In the step of preparing maleic anhydride boron nitride powder, the radio frequency discharge modification treatment controls the air flow rate to be 336-343 mL / min, the treatment power to be 216-224 W, and the treatment time to be 5.8-6.2 min; The particle size of the hexagonal boron nitride powder is 90-110 nm; The mass volume ratio of the surface hydroxylated hexagonal boron nitride powder, ethyl acetate, maleic anhydride and perchloric acid is 4.7-5.2 g: 790-810 mL: 14.1-14.5 g: 117-123 mL.
6. The method for preparing a boron nitride setter according to claim 1, characterized in that: In the first compounding step, the ultrasonic oscillation has an ultrasonic time of 1.8-2.2h, an ultrasonic frequency of 35-40kHz, and an ultrasonic power of 146-155W; The mass volume ratio of the amino boron nitride fiber, dimethyl sulfoxide and maleic anhydride boron nitride powder is 9.7-10.2 g: 246-255 mL: 4.6-5.0 g.
7. The method for preparing a boron nitride setter according to claim 1, characterized in that: In the secondary compounding step, the ultrasonic treatment has an ultrasonic time of 35-40 min, an ultrasonic power of 104-115 W, and an ultrasonic frequency of 22-27 kHz; The mass ratio of the deionized water, the primary complex, the aluminum nitrate aqueous solution, the tartaric acid solution, the hexadecyltrimethylammonium bromide, and the γ-glycidyloxypropylmethyldiethoxysilane is 49.2-50.6:9.8-10.2:66.4-67.0:9.0-9.5:1.0-1.3:0.72-0.77; The mass concentration of the aluminum nitrate aqueous solution is 2.8-3.3%; The mass concentration of the tartaric acid solution is 1.8-2.2%; The mass concentration of the ammonia solution is 20-24%.
8. The method for preparing a boron nitride setter according to claim 1, characterized in that: The cold isostatic pressing step comprises adding the dry powder into a cold pressing mold, compacting the powder, and placing the powder into a cold isostatic press for cold isostatic pressing, wherein the pressure of the cold isostatic pressing is controlled to be 70-100 MPa, and the holding time is 10-20 min to obtain a blank.
9. The method for preparing a boron nitride setter according to claim 1, characterized in that: The vacuum sintering step is to load the blank into a vacuum high-temperature furnace, sinter it in a nitrogen atmosphere, control the vacuum degree to 8-12Pa, the sintering temperature to 1850-2000°C, and the insulation time to 4.0-8.0h, and cool it to room temperature to obtain a boron nitride support plate.
Citation Information
Patent Citations
Treatment method for burning board
CN102627474A
Heat-conducting flame-retardant polyolefin-based composite material and preparation method thereof
CN114854125A